Physical damage caused during loading and unloading of Nupro's products / Shamsul Arifin Sulaiman - Sulaiman, Shamsul Arifin
Nutritional Products (M) Sdn Bhd or better known as Nupro is a well established food manufacturer in our country today. The Company has defined that the physical damage during loading and unloading as its area of concern.